ANALISIS PERILAKU KONSUMEN ELEKTRONIK PADA ONLINE-MARKETPLACE - Finisica Patrikha; Rony Setawan (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
This study was conducted to analyze consumer behavior in buying electronic devices through online-marketplaces based on consumer perceptions of brands, sellers' country of origin, store criteria, prices and service quality. Descriptive analysis is used to determine respondents' perceptions. A total of 134 respondents were obtained from respondents who filled out the questionnaire in full. The results showed that consumer perception of the brand, and the seller's country of origin became an important consideration in deciding to purchase electronic products through the online marketplace.